Comparative Study of Patent Protection for Computer Software in a Sino-EU-US Context - Uotila, Jon (My University, 2019)
A patent basically gives its holder monopoly for the patented subject matter, which is why strong patent rights often are criticized for conflicting with the open and free standards that benefit the public. Only by being the holder of one crucial patent within a standard technology, the holder is in a position to slow down or even fully stop the standardization process. The fast progress of computer technology makes defining the scope of the protection the law should afford computer programs quite difficult. The purpose of this thesis is to examine how the application process, and intellectual property right protection for software patents differ in different legal systems. Software patents provide protection for the software, but globally there is no one legal definition of a software patent. This means that the first thing to establish, is how a software patent is defined in different legal systems, after which this thesis will move on to consider the actual main research question of the thesis. The main question that will be considered in this thesis is how the protection a software patent provides differs between selected legal systems? The selected legal systems, i.e. the territorial scope of this paper will include the USA, the EU, and China. These three legal systems were chosen because of their substantial size and importance both as general markets, but even more importantly as highly competitive markets for software. Some attention will also be paid to copyright, as the form of intellectual property protection that preceded patents as the primary protection form for software. The thesis will examine the protection each legal system offers individually, but the overarching issue regarding this thesis will be a comparison between the legal systems. The legal systems will be compared to each other, in order to identify their common and unique characteristics, ending up in a discussion for an ideal legal system, consisting of the best parts from the legal systems, in the view of the patent holder and society as a whole. Business methods and software are among the most debated subjects within patent law, be-cause these areas are considered far too broad in scope, the reason behind many “patent troll” lawsuits, doubtful to conquer the prior art requirement because of loose disclosure requirements, and in general not worthy of patent protection. During the years, solutions to the sup-posed problems of business method and software patents have been short lived. Solution proposals and approaches have been accepted and rejected at a fast rate globally.
Keywords: IPR, software, China, USA, EU, patent, subject-matter